Knowledge and Attitude towards the Gradual Reduction of Salt in Bread – an Online Survey. (13th November 2019) - Costa, A; Costa, L; Santos, J; Braz, P; Santos, M; Brazão, R; Lopes, I; Guerreiro, A; Alves, J; Caldas de Almeida, T
Abstract: Background: Bread is one of the main sources of salt intake in Portugal. Based on this evidence, a protocol signed between national Health Sector and the Associations of Industrial Bakeries, in 2017, established gradually decrease salt in bread until 2021. This measure also targets schools' available bread, this should not exceed 1g salt, to end of 2018. A pilot Health Impact Assessment (HIA) aims to assess the potential impact on salt reduction in bread on the eating habits of children (6-18 years) and their families. Methods: A questionnaire is being performed to assess the effect of this measure. The first version was designed by a panel of 11 experts (content validity), following the plain text principles. A external specialist revised it for facial validity. A pilot was tested. Thereafter, a REDCap online survey of "Knowledge and Attitude towards the Gradual Reduction of Salt in Bread" questionnaire was finalized. The target group is the parents or guardians of children and young persons, of School Clusters in the south of Portugal. Results: Final online survey totalizes 33 items, divided into four blocks: 1.Knowledge and General literacy data, 2.Domestic Consumption, 3.Scholar consumption and 4.Sociodemographic. An adult responsible for the child/young person should answer the survey. Access is possible through a REDCap link, using computers available in the School Cluster, or other manner suitable for the purpose. Conclusions: This survey will contribute to the identification of modifiable behaviors related with salt intake. Such evidence may eventually provide the opportunity for new strategies in this area. Key messages: Health Impact Assessment as a procedure to assess the effects of measures and policies on human health. Questionnaires are a rapid tool to access perceptions, attitudes and knowledge.